PENGARUH HARGA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI SPBU 7593741 DI KOTA BAUBAU - Hasni (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to examine the effect of price and location on consumer purchasing decisions at SPBU 7593741 in Baubau City. The research employed a quantitative approach with a sample of 80 consumers selected using the Slovin formula. Data were collected through structured questionnaires and analyzed using multiple linear regression analysis. The findings reveal that price does not have a significant effect on purchasing decisions, as fuel prices are standardized and regulated by the government. Conversely, location demonstrates a positive and significant influence on consumer behavior, indicating that strategic positioning and accessibility are critical factors in attracting customers. Simultaneously, both variables significantly affect purchasing decisions, with a coefficient of determination of 40.2%, suggesting that other factors also contribute to consumer choices. These results emphasize the importance of location optimization in enhancing competitive advantage within the fuel retail industry.